2022
DOI: 10.3390/diagnostics12040924
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Hemorrhagic Encephalitis in COVID-19 Patients: A Case Series and Review

Abstract: Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) is an ongoing pandemic that has affected over 400 million people worldwide and caused nearly 6 million deaths. Hemorrhagic encephalitis is an uncommon but serious complication of COVID-19. The etiology of this disease is multifactorial, including secondary to severe hypoxemia, systemic inflammation, direct viral invasion, hypercoagulability, etc. The clinical spectrum of COVID-19-related hemorrhagic encephalitis is also varied, ranging from leukoenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Our results are consistent with Kandemirli et al study, which suggested that one of the most common imaging finding was cortical signal abnormalities on FLAIR images [ 14 ]. Presence of FLAIR abnormalities and microhemorrhages has been reported in other studies as well [ 5 , 15 , 16 , 17 ]. Some studies have proposed leptomeningeal enhancement; however, majority of our patients did not undergo contrast-enhanced images.…”
Section: Discussionsupporting
confidence: 76%
“…Our results are consistent with Kandemirli et al study, which suggested that one of the most common imaging finding was cortical signal abnormalities on FLAIR images [ 14 ]. Presence of FLAIR abnormalities and microhemorrhages has been reported in other studies as well [ 5 , 15 , 16 , 17 ]. Some studies have proposed leptomeningeal enhancement; however, majority of our patients did not undergo contrast-enhanced images.…”
Section: Discussionsupporting
confidence: 76%
“…Several cases developed neurological impairment following respiratory symptoms. The latency between the onset of the infection with respiratory manifestations and the onset of neurological complications varied between 3 days and 41 days [ 12 , 24 , 27 , 28 , 30 , 32 , 34 , 36 , 37 , 43 , 45 , 51 , 56 , 58 , 64 , 65 , 70 , 76 , 80 , 81 , 82 , 83 , 85 , 86 , 89 , 90 , 91 , 93 , 94 ]. Overall, 13 patients were intubated and mechanically ventilated due to respiratory distress; in these cases, the detection of neurological impairment happened when sedation was interrupted, with latency ranging between 4 and 38 days depending on the case [ 27 , 32 , 34 , 76 , 80 , 82 , 85 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until 2021, therapeutical plasmapheresis and immunosuppressive drugs were rarely prescribed. After the first period of the COVID-19 pandemic, immunomodulating agents, in particular IVIG and tocilizumab, plasmapheresis, and convalescent’s serum, have been used more often, with good response [ 21 , 51 , 59 , 60 , 70 , 81 , 83 , 88 ], except for the most severe cases, like in ANHE.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial number of patients having a COVID-19 infection had acute cerebrovascular events, including ischemic stroke [ 4 ]. The general incidence of encephalitis in COVID-19 patients is less than 1 percent, but may reach as high as 6 to 7 percent in patients with severe illness [ 10 ]. The clinical symptoms, such as a low state of consciousness, seizures, headache, and motor impairments, are comparable to those of other types of encephalitis; however, the mortality rate was determined to be around 13 percent, which is considerably higher compared with other types of encephalitis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%